THE IMPACT OF DISCOVERY LEARNING ON HIGHER-ORDER THINKING SKILLS IN CHEMISTRY: A META-ANALYSIS - Ardila, Mutia; Samosir, Rafidah Almira; Pratiwi, Alfira Julian; Kurniawan, Ekin Dwi Arif; Ridho, Dimas; Sa’diyah, Halimatus (UIN AR-RANIRY, 2025)
This research examines the effect of the discovery learning model on higher-order thinking skills in chemistry subjects at the high school level in Indonesia with a total sample of 230 students. The research method is a meta-analysis study with a range of research data from 2015-2024 based on Google Scholar indexed by Sinta. Heterogeneity test analysis using JASP version 0.8.5 shows a τ² value of 0.236 and a τ value of 0.485, with an I² value approaching 100% (CI: 74.015%–98.358%). The results indicate a high level of heterogeneity (98.358%). Therefore, a random effects model is used in the analysis. The meta-analysis results suggest that discovery learning significantly affects higher-order thinking skills (z = 4.730; p < 0.001; 95% CI). Funnel plot and Egger's tests did not show publication bias, supported by a fail-safe N value 488. The results of this study reinforce empirical evidence that discovery learning is a practical approach to chemistry learning.